Poiretia latifolia e Poiretia tetraphylla: estudo dos óleos voláteis e atividades biológicas preliminares - Silva, Carla Porto da (2005)
The essential oils from the aerial parts of leaves and flowers of Poiretia latifolia and Poiretia tetraphylla, were analysed by GC, GC/MS and Enantioselective Gas Chromatography (EGC). Forty five constituents were identified from the essential oils. The major constituents of the essential oils of P. latifolia, dominated by monoterpenos, were carvone (50-69%), limonene (13-24%) and trans-dihidrocarvone (8- 18%). The essential oil from leaves of P. tetraphylla was dominated by sesquiterpenes, where nerolidol-E (17-30%), β-cariofilene (5-16%) and germacrene-D (3-9%) were the major constituents. The essential oils from P. latifolia shows activity against brine shrimp assay (LC50 = 67 - 85 μg mL-1), and exhibited antimicrobial activity against some gram-positive and gram-negative bacteria, and some yeasts, while the essential oil from leaves of P. tetraphylla was inactive.